A first-in-human phase I study of SAR125844, a selective MET tyrosine kinase inhibitor, in patients with advanced solid tumours with MET amplification. (December 2017) - Angevin, Eric; Spitaleri, Gianluca; Rodon, Jordi; Dotti, Katia; Isambert, Nicolas; Salvagni, Stefania; Moreno, Victor; Assadourian, Sylvie; Gomez, Corinne; Harnois, Marzia; Hollebecque, Antoine; Azaro, Analia; et al.
Abstract: Purpose: Dysregulated MET signalling is implicated in oncogenesis. The safety and preliminary efficacy of a highly selective MET kinase inhibitor (SAR125844) was investigated in patients with advanced solid tumours and MET dysregulation. Methods: This was a phase I dose-escalation (3 + 3 design [50–740 mg/m 2 ]) and dose-expansion study. In the dose escalation, patients had high total MET (t-MET) expression by immunohistochemistry (IHC) or MET amplification by fluorescence in situ hybridisation. In the dose expansion, patients had MET amplification (including a subset of patients with non-small cell lung cancer [NSCLC]) or phosphorylated-MET (p-MET) expression (IHC). Objectives were determination of maximum tolerated dose (MTD) of once-weekly intravenous SAR125844 based on dose-limiting toxicities; safety and pharmacokinetic profile; preliminary efficacy of SAR125844 MTD in the expansion cohort. Results: In total, 72 patients were enrolled: dose escalation, N = 33; dose expansion, N = 39; 570 mg/m 2 was established as the MTD. Most frequent treatment-emergent adverse events (AEs) were asthenia/fatigue (58.3%), nausea (31.9%), and abdominal pain, constipation, and dyspnea (27.8% for each); 58.3% of patients reported grade 3 AEs (19.4% were treatment related). Of the 29 evaluable patients with MET amplification treated at 570 mg/m 2, five achieved a partial response, including four of 22 with NSCLC; 17 patients had stable disease. No response was observed in patients with high p-MET solid tumours. There was no correlation between tumour response and t-MET status or MET gene copy number. Conclusion: The MTD of once-weekly SAR125844 was 570 mg/m 2 ; SAR125844 was well tolerated, with significant antitumour activity in patients with MET -amplified NSCLC. Clinical trial registration number:NCT01391533 Highlights: SAR125844 was well tolerated in patients with solid tumours and MET dysregulation. SAR125844 was efficacious in MET -amplified tumours with partial responses observed. Significant antitumour activity was observed in patients with MET -amplified NSCLC.